Pendekatan Struktural Dalam Menganalisis Drama Kereta Kencana Karya WS Rendra - M. Nur Kholis; Akhmad Fatoni (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Literature serves as a mirror reflecting the social and cultural dynamics of society. This serves as the foundation for analyzing the play